Cross-Sectional and Longitudinal Evaluation of the Social Network Use Disorder and Internet Gaming Disorder Criteria - Bouna-Pyrrou, Polyxeni; Aufleger, Birte; Braun, Simona; Gattnar, Manja; Kallmayer, Sofia; Wagner, Helena; Kornhuber, Johannes; Mühle, Christiane; Lenz, Bernd (Frontiers in Psychiatry, 2018)
Background: The inclusion of internet gaming disorder (IGD) as a condition warranting more research in the DSM-5 has led to a rapid increase of research on addictive internet activities. Further evaluation of the criteria for IGD and social network disorder (SND) is needed. Objective: To assess the internal consistency, construct validity, retest-reliability, and long-term stability of SND and IGD criteria in German-speaking cohorts. Method: We conducted total and sex-specific analyses on data from two cross-sectional and longitudinal studies, one sample of 192 participants enriched for internet use and another community-based sample of 2316 individuals. Results: First, independent from assessment setting (online, telephone, on-site) and gender, we found acceptable to good internal consistency for SND and IGD criteria (Cronbach's α 0.690–0.774 for SND and 0.743–0.866 for IGD, respectively). Second, positive Spearman correlations between the sum of affirmed criteria and established scales of pathological internet use (ρ 0.395–0.783) and time spent on the social networking sites or internet gaming (ρ 0.317–0.761) confirmed convergent validity. Moreover, the sum of affirmed criteria related positively to attentional impulsivity (ρmax 0.311), urgency (ρ 0.124–0.200), and neuroticism (ρmax 0.210), and negatively to perseverance (ρ −0.245— −0.098) and conscientiousness (ρmin −0.257). Finally, SND and IGD criteria showed high retest stability (SND ρ 0.653–0.826, IGD ρ 0.714–0.825, respectively). However, participants scored higher on SND and IGD scales during the online compared to the on-site assessment. The 2-year follow-up revealed an increase in affirmed SND and IGD criteria. Conclusion: Our data support good psychometric properties of the SND and IGD criteria and outline the addictive potential of social networking sites.